Lean culture for a successful lean manufacturing implementation: An empirical evidence from Malaysian manufacturing industry - Norhana, Mohd Aripin; Gusman, Nawanir; Suhaidah, Hussain (Penerbit Universiti Malaysia Pahang, 2023)
Although lean has gained many accomplishments, 90% of the manufacturers that implemented lean failed to sustain the implementation, and these results have led academics to consider lean culture as a soft lean approach for successful lean implementation. This research is aimed to investigate the role of lean culture for a successful lean implementation. This survey-based was a cross-sectional study with 151 final respondents from discrete manufacturers in Malaysia. The samples were selected using a cluster sampling procedure from medium and large manufacturing companies registered with the Federation of Manufacturers Malaysia (FMM). The data was analyzed using SmartPLS 4.0 software. The result showed evidence that lean manufacturing implementation is positively impacted by lean culture. This study contributes to the body of knowledge and widens the bounds of the current literature, and offers insight to the lean practitioners on lean implementation techniques to strategize the roadmap and assure continuous execution by considering the role of lean culture.